The Return of Ikenga - Ohuka, Chukwuemeka (Macmillan Nigeria, 1980)
This is an exciting tale of plot and counter polt set in pre-colonial Eastern Nigeria. Since the ageing King, Eze Igwekala,had only one young son, the weakness of his position was successfully exploited by his powerful opponent, Igbonoba.
Keywords: Fiction-Nigeria (English)